Laying the Groundwork for Participatory Budgeting – Developing a Deliberative Community and Collaborative Governance: Greater Geraldton, Western Australia - Hartz-Karp, Janette (Dept. of Political Science ,Auburn University, US, 2012)
Participatory Budgeting (PB), an institutional innovation to promote democratic change, is a form of collaborative governance in which citizens are involved in decision-making processes about how to spend part or all of available government funds. Like the broader concept of democracy, for PB to be effective, there needs to be an ongoing participatory process that involves the building of civic capacity and infrastructure. This paper focuses on a particular attribute of civic efficacy, that of deliberative public engagement, defined as collaborative problem solving through informed, inclusive, egalitarian processes with the outcomes influencing policy, decisions and/or collaborative action. It is argued that to be a deep democratic reform, PB needs to be more intentionally deliberative than usually practiced, within an environment that nurtures civic collaboration and empowerment. In the current situation of disaffected, often angry and/or cynical citizenry, without resorting to revolution, overcoming the pervasive sense of impotence to effect real change is not easy. It requires ongoing effort to create the civic capacity, policies and the institutions that will enable everyday people to work together with decision-makers to achieve collaborative public wisdom, decisions and action. For PB to avoid being merely a superficial band-aid to the perceived malaise of our democratic systems, we contend that the culture in which it is situated needs to be nurtured and stewarded to be more collaborative, considered and egalitarian. The deliberative democracy process instituted over a number of years in Greater Geraldton, Western Australia, shows how some of the preconditions for an effective participatory budgeting initiative could be achieved. The lessons learned are widely applicable to other western democracies, and potentially, other forms of governance.